Chemical probes of Skp2-mediated p27 ubiquitylation and degradation. Issue 7 (13th June 2018) - Lough, Lea; Sherman, Dan; Ni, Eric; Young, Lauren M.; Hao, Bing; Cardozo, Timothy
Abstract : A meta-analysis of Skp2 inhibitors based on bioactivity, structure, and medicinal chemistry was used to identify validated Skp2 pharmaceutical hits. Abstract : Skp2 is a member of the F-box family of proteins that serve as substrate-specific adaptors in Skp1–CUL1–ROC1–F-box (SCF) E3 ubiquitin ligases. Skp2 (Fbxl1) directly binds to the tumor suppressor p27 in the context of the SCF Skp2 E3 ubiquitin ligase to ubiquitylate and target-phosphorylated p27 for proteasomal degradation. As p27 is a powerful suppressor of growth in a variety of cells, and as Skp2 is also overexpressed in many human cancers, Skp2 is considered an oncogene and an intriguing drug target. However, despite 20 years of investigation, a valid chemical inhibitor of Skp2-mediated degradation of p27 has not been identified. Recently, an increasing number of compounds designed to have this bioactivity have been reported. Here, we conduct a meta-analysis of the evidence regarding bioactivity, structure, and medicinal chemistry in order to evaluate and compare these Skp2 inhibitor compounds. Despite chemically diverse compounds with a wide array of Skp2-mediated p27 ubiquitylation inhibition properties reported by several independent groups, no current chemical probe formally qualifies as a validated pharmaceutical hit compound. This finding suggests that our knowledge of the structural biochemistry of the Skp2–p27 complex remains incomplete and highlights the need for novel modes of inquiry.